Prioritization and transparency in software development: An action research in public administration - Pinheiro, Álvaro; Martins, Nilo; Soares, Melina; Neto, Geraldo; Santos, Wylliams (Anais do Brazilian Workshop on Social Network Analysis and Mining (BraSNAM), 2021)
The prioritization of requirements is a critical activity in quality assurance. However, in public institutions, prioritization faces conflicts with financial constraints. Problem: Increasing the complexity of requirements. Objective: Proposition of a Kanban method to improve the transparency of activities and facilitate prioritization. Method: An action research carried out in two cycles at the Attorney General's Office of the State of Pernambuco, involving the development team and public managers. Result: The presentation of the method's effectiveness as a mechanism facilitating transparency and as a support to management in prioritization.